Reflexiones sobre la enseñanza de la química. (2004)
lt is possible enrichrnent the conceptions that teachers possess as far as science and its teaching. Here, the  reflection is to be made with a group of teachers about the different styles that lab working in the chemistry class. In this is recognized the kind of procedures that are privileged but also  the epistemological point. Through this means the teacher's guidelines of the lab work are analyzed. Then, they build some  alternative options that replace them. The result shows that the reflection about practice itself allows the evolution of the chernistry teacher's conceptions, which are exposed on the type of experiments proposed to their students.